ISOLASI DAN KARAKTERISASI SENYAWA FENOLIK DARI DAUN PUTAT (Planchonia valida Blume) (ISOLATION AND CHARACTERIZATION OF PHENOLIC COMPOUND FROM PUTAT LEAVES (Planchonia valida Blume)) - syafri syamsudin; Andi Hairil Alimuddin; Berlian Sitorus (Indonesian Journal of Pure and Applied Chemistry, 2022)
Gallic acid have been isolated from the leaves of the Putat plant (Planchonia valida Blume). This study aimed to isolate and characterize isolates from Putat leaves by phytochemical and FTIR spectrophotometry. The research procedures included extraction by maceration, partitioning by fractionation, vacuum liquid chromatography (KCV), gravity column chromatography (KKG), thin layer chromatography (TLC), and FTIR analysis. A total of 1400 grams of putat leaf powder was macerated to produce 159.243 grams (11.38%) of methanol extract. A total of 101 grams of methanol extract was dechlorophyllated to obtain 21.430 grams (21.21%) of dechlorophyllated extract. The dechlorophyllated extract was partitioned gradually with n-hexane and ethyl acetate to produce n-hexane fractions of 0.341 grams (1.591%), and ethyl acetate of 10.143 grams (47.33%), and methanol of 9.170 grams (42.79%). A phytochemical test showed that in the dechlorophyllated extract, the methanol and ethyl acetate fractions contained alkaloids, phenolics, flavonoids, and terpenoids while the n-hexane fraction contained alkaloids and flavonoids. A total of 7 grams of ethyl acetate fraction was fractionated by vacuum liquid chromatography to produce fractions B1 to B8. The B4 fraction was continued to the separation step by gravity column chromatography so that the fractions S1 to S9 were obtained. The S4 fraction was continued to the separation stage using preparative thin layer chromatography (TLC) to produce isolates S4.1 to S4.5. Isolate S4.1 was tested for purity by two-dimensional TLC showed that the isolate was not pure. The results of the phytochemical test with 5% FeCl3 spray reagent indicated a positive phenolic compound which was strengthened by FTIR characterization of the presence of –OH, -CH aromatic, -CH aliphatic, C=C, C=O and C-O goups. Based on these results, it was concluded that the isolate from the dechlorophyllated extract of Putat leaves belonged to phenolic compounds.